2010
DOI: 10.1186/1477-7525-8-57
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of a visual analog scale for the assessment of anxiety

Abstract: BackgroundFast-acting medications for the management of anxiety are important to patients and society. Measuring early onset, however, requires a sensitive and clinically responsive tool. This study evaluates the psychometric properties of a patient-reported Global Anxiety - Visual Analog Scale (GA-VAS).MethodsData from a double-blind, randomized, placebo-controlled study of lorazepam and paroxetine in patients with Generalized Anxiety Disorder were analyzed to assess the reliability, validity, responsiveness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(139 citation statements)
references
References 36 publications
2
128
1
Order By: Relevance
“…Cole and colleagues 401 argued that anchor values should be used in considering individual change, and for group-level change distribution (SEM) estimates were preferable to SES (0.5 SDs) estimates because the latter does not account for the internal consistency of the measurement being used. A study by Williams and colleagues 402 presented a wide range of values but then considered clustering of values within this range and reported the range within which values tended to cluster. Barber and colleagues 403 calculated 95% CIs for each of the methods used and, finding overlap, used an anchor estimate arguing that the distribution method estimate supported it.…”
Section: Combining Results Derived From Multiple Methodsmentioning
confidence: 99%
“…Cole and colleagues 401 argued that anchor values should be used in considering individual change, and for group-level change distribution (SEM) estimates were preferable to SES (0.5 SDs) estimates because the latter does not account for the internal consistency of the measurement being used. A study by Williams and colleagues 402 presented a wide range of values but then considered clustering of values within this range and reported the range within which values tended to cluster. Barber and colleagues 403 calculated 95% CIs for each of the methods used and, finding overlap, used an anchor estimate arguing that the distribution method estimate supported it.…”
Section: Combining Results Derived From Multiple Methodsmentioning
confidence: 99%
“…DAS and VAS-A were strongly correlated, and the VAS-A (12) evaluated the psychometric properties of a patient-reported Global Anxiety VAS (GA-VAS) for measuring anxiety in clinical trials assessing pharmaceutical treatment for generalized anxiety disorders. They reported that the GA-VAS was reliable, responsive, and valid in assessing improvement in anxiety symptoms within 1 week of beginning administration of anxiolytic drugs (12).…”
Section: Discussionmentioning
confidence: 99%
“…This problem would be remedied by prospective research to obtain a normallydistributed data set. In relation to details of the form of the scales, we speculate that a more precise way approached from another viewpoint might be possible, for example, utilizing a visual analogue scale (VAS) [35][36][37][38][39] or a numerical rating scale (NRS) [40,41] for the ratings by psychiatrists, both of which range from 0 to 10, for the scores that we substituted for the clinical impression (although the true estimation of their validity is in flux at present [42][43][44][45][46][47][48]). We chose instead the ordinal CGI-SCH scores, which range ordinarily from 1 to 7 (taking "0" as "not assessed"), to express the clinicians' global impresssion of illness with schizophrenic patients.…”
Section: Figure 5 An Example Of a Potential Modified 18-item Bprs Mmentioning
confidence: 99%